Hsp90 as a Myokine: Its Association with Systemic Inflammation after Exercise Interventions in Patients with Myositis and Healthy Subjects - Švec, Xiao; Štorkánová, Hana; Špiritović, Maja; Slabý, Kryštof; Oreská, Sabína; Pekáčová, Aneta; Heřmánková, Barbora; Bubová, Kristýna; Česák, Petr; Khouri, Haya; Amjad, Gulalai; Mann, Heřman; et al. (International journal of molecular sciences, 2022)
Compelling evidence supports the health benefits of physical exercise on the immune system, possibly through the molecules secreted by the skeletal muscles known as myokines. Herein, we assessed the impact of exercise interventions on plasma Heat shock protein 90 (Hsp90) levels in 27 patients with idiopathic inflammatory myopathies (IIM) compared with 23 IIM patients treated with standard-of-care immunosuppressive therapy only, and in 18 healthy subjects undergoing strenuous eccentric exercise, and their associations with the traditional serum markers of muscle damage and inflammation. In contrast to IIM patients treated with pharmacotherapy only, in whom we demonstrated a significant decrease in Hsp90 over 24 weeks, the 24-week exercise program resulted in a stabilization of Hsp90 levels. These changes in Hsp90 levels were associated with changes in several inflammatory cytokines/chemokines involved in the pathogenesis of IIM or muscle regeneration in general. Strenuous eccentric exercise in healthy volunteers induced a brief increase in Hsp90 levels with a subsequent return to baseline levels at 14 days after the exercise, with less pronounced correlations to systemic inflammation. In this study, we identified Hsp90 as a potential myokine and mediator for exercise-induced immune response and as a potential biomarker predicting improvement after physiotherapy in muscle endurance in IIM.
Keywords: kosterní svaly; exercise; Healthy Volunteers; zánět; Cytokines; biologické markery; idiopathic inflammatory myopathies; Biomarkers; skeletal muscles; HSP90 Heat-Shock Proteins; zdraví dobrovolníci pro lékařské studie; cytokiny; Chemokines; lidé; Immunosuppressive Agents; Exercise Therapy; Muscle, Skeletal; myozitida; Inflammation; proteiny tepelného šoku HSP90; heat shock protein 90; Myositis; cytokines; chemokiny; terapie cvičením; myokines; imunosupresiva; Humans